2019
DOI: 10.1093/ofid/ofz416
|View full text |Cite
|
Sign up to set email alerts
|

Higher MICs (>2 mg/L) Predict 30-Day Mortality in Patients With Lower Respiratory Tract Infections Caused by Multidrug- and Extensively Drug-Resistant Pseudomonas aeruginosa Treated With Ceftolozane/Tazobactam

Abstract: BackgroundCeftolozane/tazobactam (C/T) efficacy and safety in ventilator-associated pneumonia (VAP) is being evaluated at a double dose by several trials. This dosing is based on a pharmacokinetic (PK) model that demonstrated that 3 g q8h achieved ≥90% probability of target attainment (50% ƒT > minimal inhibitory concentration [MIC]) in plasma and epithelial lining fluid against C/T-susceptible P. aeruginosa. The aim of this study was to evaluate the efficacy of different C/T doses in patients with lower respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
66
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(67 citation statements)
references
References 38 publications
1
66
0
Order By: Relevance
“…Similar worrisome trends for bacterial susceptibility to available antimicrobials have been reported by other investigators as well [ 60 , 61 ]. Most worrisome is the increasingly recognized presence of resistance to new antibiotics specifically developed to treat VAP [ 62 ].
Fig.
…”
Section: Epidemiology Of Nosocomial Pulmonary Infections In Ards Patimentioning
confidence: 99%
“…Similar worrisome trends for bacterial susceptibility to available antimicrobials have been reported by other investigators as well [ 60 , 61 ]. Most worrisome is the increasingly recognized presence of resistance to new antibiotics specifically developed to treat VAP [ 62 ].
Fig.
…”
Section: Epidemiology Of Nosocomial Pulmonary Infections In Ards Patimentioning
confidence: 99%
“…Third, high inactivation of C/T by derepressed AmpC organisms justifies strict monitoring of its resistance level in both Enterobacterales and Pseudomonas, particularly those associated with poor outcomes when high MICs (>2 g/mL) are observed. 10 In conclusion, in this study, we identified a mechanism that seems to be predictive of high C/T resistance levels. More prominent among bacteria that are capable of derepressing AmpC β-lactamases, mainly the E. cloacae complex (but also Pseudomonas on a minor scale), this resistance to C/T should lead to stricter use and monitoring of this drug.…”
mentioning
confidence: 51%
“…Some other points should also be considered. First, C/T was primarily designed to treat Pseudomonas infections, and because this bacterium is highly susceptible to this drug, 10 it is reasonable to conclude that Pseudomonas usually does not derepress chromosomal AmpC enzymes, even those with an extensively drug-resistant phenotype. Second, C/T is an inappropriate drug for use in empirical therapeutic approaches; it should be preserved for the specific niche for Pseudomonas infection.…”
mentioning
confidence: 99%
“…Including studies that recruited patients from multiple countries, the most common study locations were the US (N = 50), (21, 22, 24, 27-29, 33, 34, 39-41, 43-45, 50, 51, 54, 56, 57, 59, 61, 62, 68-71, 73-77, 79-85, 87-92, 94, 95, 97-100) Spain (N = 15), (26, 28, 30-32, 35-37, 42, 47, 49, 58, 66, 79, 96) and Italy (N = 13). (18,20,23,25,48,52,53,55,64,67,72,79,86) A variety of study designs were captured: 27 were non-comparative retrospective studies, (18,19,22,24,25,28,32,33,40,41,79,81,(84)(85)(86)(87)(88)(89)(90)(91)(92)(94)(95)(96)(97)(98)(99) 14 were case series, (20, 21, 29, 31, 34-39, 42, 43, 82, 100) ve were comparative (including two cohort studies, (80,83) and three case-control studies, (23,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Five studies found mixed evidence that a delay in receipt of C/T led to worse outcomes. (18,28,30,33,39) Bassetti et al 2020 found that a signi cantly higher proportion of patients who achieved clinical success received empiric C/T and had a signi cantly shorter latency between infection onset and C/T administration (both p < 0.001). (18) Similarly, Gallagher et al 2018 found that starting C/T less than four days after positive culture was associated with signi cantly higher clinical and microbiological cure rates, and that starting C/T more than four days after positive culture was associated with signi cantly higher mortality.…”
Section: Outcomes By Treatment Characteristicsmentioning
confidence: 99%